On the utility of radium isotopes as tracers of hydrocarbon discharge - Peterson, R N; Viso, R F; MacDonald, I R; Joye, S B (Marine Chemistry, 2013)
Natural seepage of hydrocarbons commonly occurs in the Gulf of Mexico and numerous other locations around the world's oceans. In-situ quantification of discharge and transport of these hydrocarbons through the water column is somewhat limited by a lack of available tracers. Here, we consider the utility of using radium isotopes, which are commonly enriched in formation fluids contained within hydrocarbon reservoirs, as tracers of hydrocarbons discharged into the deep ocean. During a cruise in November/December 2010 through the Gulf of Mexico, radium isotopes (224Ra and 226Ra) revealed anomalous concentrations in near-bottom samples associated with the presence of hydrocarbons at several sites where hydrocarbon seepage was known to occur and observed real-time via the human-occupied vehicle Alvin. These tracers also indicated the presence of near-bottom hydrocarbons in the vicinity of the Macondo wellhead where the Deepwater Horizon blowout occurred months earlier. These hydrocarbons are presumed to originate from nearby gas seeps later identified by water column sonar returns. The short half-life of 224Ra (3.66 days) suggests that anomalously high unsupported activities of this isotope must be derived from recent (days to weeks) discharge. Sampling at the sediment–water interface confirmed that the source of the water column radium isotope anomalies is likely benthic sources. These results suggest that radium isotopes may serve as useful tracers of hydrocarbons in such an environment, and we outline steps required to quantify discharge rates and transport time scales with these tracers.
Keywords: HOV Alvin (Human Occupied Vehicle)